2014
DOI: 10.1136/bmjopen-2014-004827
|View full text |Cite
|
Sign up to set email alerts
|

Do rapid BMI growth in childhood and early-onset obesity offer cardiometabolic protection to obese adults in mid-life? Analysis of a longitudinal cohort study of Danish men

Abstract: ObjectiveSome obese individuals have no cardiometabolic abnormalities; they are ‘metabolically healthy, but obese’ (MHO). Similarly, some non-obese individuals have cardiometabolic abnormalities, that is, ‘metabolically at risk, normal weight’ (MANW). Previous studies have suggested that early-onset obesity may be associated with MHO. We aimed to assess whether body mass index (BMI) in childhood and early-onset obesity are associated with MHO.SettingGeneral population longitudinal cohort study, Denmark.Partici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 53 publications
(52 reference statements)
1
11
0
Order By: Relevance
“…The current study added to this knowledge base by examining the associations between obesity level adjusting for gender and pubertal stage categories and by differentiating the two definitions, including insulin resistance. We recognise, though, that our study would have been further strengthened by studying the association of the duration and timing of the onset of obesity , as well as fat mass degree and distribution , with metabolic phenotypes.…”
Section: Discussionmentioning
confidence: 98%
“…The current study added to this knowledge base by examining the associations between obesity level adjusting for gender and pubertal stage categories and by differentiating the two definitions, including insulin resistance. We recognise, though, that our study would have been further strengthened by studying the association of the duration and timing of the onset of obesity , as well as fat mass degree and distribution , with metabolic phenotypes.…”
Section: Discussionmentioning
confidence: 98%
“…Collectively, the data indicate that MHO children are more likely to be younger (and in earlier stages of puberty) and female, of high birth weight with less visceral fat, exhibiting preserved insulin sensitivity, high adiponectin concentrations, altered ghrelin levels, more favorable lipid profiles, reduced concentrations of transaminases and uric acid, and without hepatic steatosis . Although early weight gain was originally identified as a determinant of childhood MHO, a larger study of Danish men for whom childhood BMI was available failed to find robust evidence to support a role for either rapid BMI growth or early‐onset obesity in the development of MHO . Aside from laboratory and clinically based predictors, limited data regarding the roles of environmental, lifestyle, behavioral, or genetic factors in determining MHO status among children exist.…”
Section: Mho In Childhood and Adolescencementioning
confidence: 96%
“…[17][18][19][22][23][24][25][26][27][28] Although early weight gain was originally identified as a determinant of childhood MHO, 23 a larger study of Danish men for whom childhood BMI was available failed to find robust evidence to support a role for either rapid BMI growth or early-onset obesity in the development of MHO. 29 Aside from laboratory and clinically based predictors, limited data regarding the roles of environmental, lifestyle, behavioral, or genetic factors in determining MHO status among children exist. Prince et al 17 examined lifestyle predictors of MHO among 8-to 17-year-olds attending a weight-management clinic.…”
Section: Mho In Childhood and Adolescencementioning
confidence: 99%
See 1 more Smart Citation
“…() found higher BMI at ages 2–11 years to protect obese adults ( n = 499) from the metabolic syndrome, whereas Howe et al . () found no robust evidence that rapid BMI gain between 7 and 13 years was protective for cardio‐metabolic health in obese Danish men ( n = 284). The two studies that have investigated early‐onset obesity also reported equivocal results (Brochu et al .…”
Section: Body Size Trajectories and Life Course Exposuresmentioning
confidence: 93%